GENOTOXIC EFFECT OF APPLE GREEN COLOUR ADDITIVE ON GERM CELLS OF SHORT HORNED GRASSHOPPER POECILOCERUS PICTUS F. (INSECTA: ORTHOPTERA: ACRIDIIDAE) - AMIYABALA SATPATHY; PRAFULLA K. MOHANTY (The Bioscan, 2012)
Colour additives, preservatives and food retention agents in our daily food is a matter of serious concern. Such food additives might be mutagenic to human genome. The long term exposure of humans to different synthetic food additives leads to several health hazards,of which genotoxicity is of prime importance.The investigation on the effect of Apple green which is a combination of chemical compounds such as Tartrazine (1914 0), Brilliant Blue (42090) and Sodium chloride of Alpana’s Natraj brand on grasshoppers shows that this compound induces chromosomal aberrations significantly with increase in concentration and exposure duration of the organism to such chemical. Hence, nonuse of the stated colour additive is suggested for the better health status of human beings.